SYNTHESIS OF BIODIESEL FROM GMELINA ARBOREA DEAD LEAVES WITH CALCIUM OXIDE CATALYST (FUDMA JOURNAL OF SCIENCES, 2020)
The depletion of fossil fuel, increase in the world population and environmental hazard associated with fossil fuel have rechanneled the world’s interest toward finding a new alternative source of energy that is renewable and sustainable. Forest resources such as biomass wastes can serve as an alternative source of energy due to their availability, renewability, sustainability, biodegradability and environmentally friendly. Reuse of solid wastes by converting them to something useful will better the live of the communities they are generated. In this investigation, Gmelina arborea dead leaves were collected, pulverized, sieved and hydrolyzed with Calcium oxide catalyst and distilled water. The product was filtered, dried with magnesium sulphate and then analyzed with GC-MS. The results of the analysis contained 77.64 g (54.59 %) biodiesel, 25.75 g (18.14 %) furfural and its derivatives, 15.18 g (10.69 %) free fatty acids, 11.49 g (8.03 %) benzene derivatives and 11.996 g (8.45 %) others. The results indicated that biorefining of Gmelina arborea leaves would provide important chemicals raw materials capable of replacing some from petroleum products for our industries. Instead of burning these dead leaves that can cause pollution to the environment, they are rather be refined to produce biofuel and oleochemicals for industrial applications than to be wasted. However, biodiesel produced from these needs purification to obtain high grade fuel for use in compression ignition engines.
Keywords: biodiesel, dead leaves, Gmelina arborea, waste reuse